Military and Political Agitation of Polish-Lithuanian Commonwealth against Ivan Terrible (Materials of Various Literary Monuments of Livonian War Era) - I. A. Prokhorenkov; N. V. Eylbart (Научный диалог, 2023)
The Livonian War led to an increase in the number of anti-Moscow works in Europe. Western authors closely followed Russia’s successes and failures in the struggle for the redistribution of the Baltic states. The main target of criticism in propaganda texts was Ivan the Terrible, who was portrayed as an enemy of Europe, equal in power to the Turkish sultan. This article analyzes the features of the anti-Russian information campaign based on various genres of texts published in the Polish-Lithuanian Commonwealth. The study of the statistical aspect of the circulation of pamphlets showed that during the later stages of the war, Polish-Lithuanian typographers significantly influenced the formation of the news field in Europe. The examined works of minor literary forms demonstrated that the description of the confrontation between the Polish-Lithuanian Commonwealth and Russia was presented in the context of a defensive war. Due to the noticeable increase in the number of propaganda texts during the reign of Stefan Batory, it was concluded that the Polish king played a primary role in the information campaign to discredit Russia. Batory understood the power of printed propaganda and invested numerous resources in tarnishing the image of the Russian ruler. As a result, by the end of the war, the Polish-Lithuanian Commonwealth managed to have a significant influence on the emerging negative image of Russia and its ruler in Europe.